Manajemen Strategik Berbasis Informasi dan Teknologi dalam Meningkatkan Daya Saing Sekolah - Diana, Eka; Uus Devi Nurjannah; Putri Fatmawati; Parati (Indo-MathEdu Intellectuals Journal, 2024)
The era of globalization and digitalization, educational institutions face new challenges to improve competitiveness. This study aims to analyze the application of information and technology-based strategic management at MA Nurul Wahid Al Wahyuni Sumberan Besuk to identify strategies to improve performance and competitive position. A qualitative approach is used with a case study type. Data collection techniques used participant observation, in-depth interviews, and document analysis with key informants of the principal, head of facilities, teachers, and students, while the data analysis used consisted of data reduction, data display, and conclusion. The results showed that despite budget and infrastructure limitations, strategic solutions such as educator training, open-source software utilization, and cloud-based service integration succeeded in improving decision-making effectiveness and operational efficiency. This provides new insights into technology adaptation strategies for educational institutions with limited resources and underscores the importance of continuous investment in infrastructure and digital iteration for continued competitiveness